Tributyrin Supplementation Protects Immune Responses and Vasculature and Reduces Oxidative Stress in the Proximal Colon of Mice Exposed to Chronic-Binge Ethanol Feeding - B. Glueck; Y. Han; G. A. M. Cresci (Journal of Immunology Research)
Excessive ethanol consumption causes adverse effects and contributes to organ dysfunction. Ethanol metabolism triggers oxidative stress, altered immune function, and gut dysbiosis. The gut microbiome is known to contribute to the maintenance of intestinal homeostasis, and disturbances are associated with pathology. A consequence of gut dysbiosis is also alterations in its metabolic and fermentation byproducts. The gut microbiota ferments undigested dietary polysaccharides to yield short-chain fatty acids, predominantly acetate, propionate, and butyrate. Butyrate has many biological mechanisms of action including anti-inflammatory and immunoprotective effects, and its depletion is associated with intestinal injury. We previously showed that butyrate protects gut-liver injury during ethanol exposure. While the intestine is the largest immune organ in the body, little is known regarding the effects of ethanol on intestinal immune function. This work is aimed at investigating the effects of butyrate supplementation, in the form of the structured triglyceride tributyrin, on intestinal innate immune responses and oxidative stress following chronic-binge ethanol exposure in mice. Our work suggests that tributyrin supplementation preserved immune responses and reduced oxidative stress in the proximal colon during chronic-binge ethanol exposure. Our results also indicate a possible involvement of tributyrin in maintaining the integrity of intestinal villi vasculature disrupted by chronic-binge ethanol exposure.